Dependence of observables in elastic scattering of intermediate energy protons by 6He from its structure - V. P. Mikhailyuk; Yu. A. Pozdnyakov (Ядерна фізика та енергетика)
In the framework of variation calculations on the basis of resonating group method with exact consideration of the Pauli principle the most probable geometric configuration of the ground state 6He nucleus (two-neutron α – 2n and linear three-cluster n – α – n) is obtained. For both configurations the calculation of observables in the elastic 721-MeV protons on 6He nucleus were carried out. As occurred, existing experimental data on elastic proton scattering (elastic scattering differential cross-section at –t ≤ 0,1 (GеV/c)2 transferred momenta) do not allow to draw a reliable conclusion as for the preference of a ground state 6 He geometric configuration obtained in the variation calculations. It is shown that experimental data for polarization and spin rotation function in the region of –t ≥ 0,1 (GеV/c)2 transferred momenta will allow to acquire more reliable conclusion, as for the most probable geometric configuration of the ground state 6 He nucleus.